Versatile RNA tetra-U helix linking motif as a toolkit for nucleic acid nanotechnology - Bui, My N. (Nanomedicine, 2017)
RNA nanotechnology employs synthetically modified ribonucleic acid (RNA) to engineer highly stable nanostructures in one, two, and three dimensions for medical applications. Despite the tremendous advantages in RNA nanotechnology, unmodified RNA itself is fragile and prone to enzymatic degradation. In contrast to use traditionally modified RNA strands e.g. 2′-fluorine, 2′-amine, 2′-methyl, we studied the effect of RNA/DNA hybrid approach utilizing a computer-assisted RNA tetra-uracil (tetra-U) motif as a toolkit to address questions related to assembly efficiency, versatility, stability, and the production costs of hybrid RNA/DNA nanoparticles. The tetra-U RNA motif was implemented to construct four functional triangles using RNA, DNA and RNA/DNA mixtures, resulting in fine-tunable enzymatic and thermodynamic stabilities, immunostimulatory activity and RNAi capability. Moreover, the tetra-U toolkit has great potential in the fabrication of rectangular, pentagonal, and hexagonal NPs, representing the power of simplicity of RNA/DNA approach for RNA nanotechnology and nanomedicine community.